PENYUSUNAN JADWAL UJIAN MATA KULIAH DENGAN ALGORITMA PEWARNAAN GRAF WELCH POWELL - Setia Astuti (JURNAL DIAN, 2011)
ln makinga schedule in our daily life, it often causes a clash or trouble.Personally it will be not a big problem since there is time tolerance and different schedule of each person.lf there are many persons on a schedule it will be a big problem which causes a big trouble.A schedule of auniversity includes variety subjects and many students. Graph coloring Welch Powell algorithm offers a good solution to know the minimum amount of days which are available for an examination, as the result there will be no schedule clash anymore for students.Keywords : graph, node,coloring, exam schedule